2001
DOI: 10.1162/089892901564225
|View full text |Cite
|
Sign up to set email alerts
|

Relative Shift in Activity from Medial to Lateral Frontal Cortex During Internally Versus Externally Guided Word Generation

Abstract: Goldberg (1985) hypothesized that as language output changes from internally to externally guided production, activity shifts from supplementary motor area (SMA) to lateral premotor areas, including Broca's area. To test this hypothesis, 15 right-handed native English speakers performed three word generation tasks varying in the amount of internal guidance and a repetition task during functional magnetic resonance imaging (fMRI). Volumes of significant activity for each task versus a resting state were derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
100
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(118 citation statements)
references
References 32 publications
15
100
1
2
Order By: Relevance
“…On the basis of our findings and in accord with previous work contrasting MPFC and LPFC functions (Crosson et al, 2001;Ochsner et al, 2004), it would seem that the lateral network is activated when one exerts task-focused controlled processes that are directed at regulating one's behavior in the context of the immediate environment. The medial network, on the other hand, may be activated when the detection of discrepancy leads to introspection about whether one is capable of responding effectively to current task demands or to consider the implications of one's current task performance for a more global selfevaluation.…”
Section: Lateral and Medial Control Networksupporting
confidence: 89%
“…On the basis of our findings and in accord with previous work contrasting MPFC and LPFC functions (Crosson et al, 2001;Ochsner et al, 2004), it would seem that the lateral network is activated when one exerts task-focused controlled processes that are directed at regulating one's behavior in the context of the immediate environment. The medial network, on the other hand, may be activated when the detection of discrepancy leads to introspection about whether one is capable of responding effectively to current task demands or to consider the implications of one's current task performance for a more global selfevaluation.…”
Section: Lateral and Medial Control Networksupporting
confidence: 89%
“…1), the preSMA receives input from the thalamus, which in turn receives input from the basal ganglia. This connection is hypothesized to be important for syllable representation and serial coordination of motor apparatus (e.g., Alario et al, 2006;Crosson et al, 2001;Hikosaka et al, 1996) as well as for the selection, initiation, and inhibition of action and movement timing control (e.g., Cunnington et al, 2006;Jaffard et al, 2008). Our SEM results showed that stuttering speakers and non-stuttering speakers differed significantly in this connection: a strong negative projection in non-stuttering speakers, but a positive projection in stuttering speakers.…”
Section: Similarities and Differences In Effective Connectivitymentioning
confidence: 63%
“…Many studies have shown a close relation between the SMA and stuttering (see Abe et al, 1993;Alm, 2004;Packman et al, 2007). Although previous studies on stuttering did not focus on the differences between the SMA proper and preSMA (e.g., Braun et al, 1997;Fox et al, 2000;Ingham et al, 2000), the preSMA, along with the basal ganglia, seems to have a closer relation with syllable representation and spatially and temporally serial coordination of motor apparatus than does the SMA proper (e.g., Alario et al, 2006;Bohland and Guenther, 2006;Crosson et al, 2001;Ferrandez et al, 2003;Hikosaka et al, 1996;Lewis et al, 2004). The preSMA ( y > 0) was also reported to be positively correlated with stuttering rate and to show deactivation during reading as compared with resting in stuttering speakers Ingham et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The supplementary motor area has been previously shown to result in speech arrest and/or anomia when stimulated (Baumgartner et al, 1996;Berger, 1995;Berger andOjemann, 1992, 1994;Fried et al, 1991;Ojemann et al, 1989;Penfield and Rasmussen, 1950;Skirboll et al, 1996), resected (Fontaine et al, 2002;Krainik et al, 2003;Laplane et al, 1977;Rostomily et al, 1991;Zentner et al, 1996), or activated in functional imaging speech experiments (Alexander et al, 1986;Blank et al, 2002;Bookheimer et al, 2000;Corson et al, 2001;Etard et al, 2000;Fiez and Petersen, 1998;Fontaine et al, 2002;Krainik et al, 2003;Petersen et al, 1989;Rosen et al, 2000;Wildgruber et al, 2001;Xiong et al, 2000). Hence the existence of white matter connectivity between the supplementary motor area and the anomia and speech arrest sites in the inferior precentral gyrus is expected.…”
Section: Discussionmentioning
confidence: 97%